Entrepreneurship : theory, process, practice - Kuratko, Donald (Australia : Cengage Learning Asia Pte Ltd, 2019)
Entrepreneurship is the the most powerful economic force known to human to human kind.
Part 1. The Entrepreneurial Mind-Set in the Twenty-First Century -- Part 2. Initiating Entrepreneurial Ventures -- Part 3. Developing the Entrepreneurial Plan -- Part 4. Growth strategies for Entrepreneurial Ventures.
Includes index.
Keywords: ENTRENEURSHIP -- UNITED STATES